Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae) - Bąkowski, Marek; Piątek, Wiktoria (Zootaxa, 2020)
This work presents the first descriptions of the pupal morphology of three species of western Palaearctic clearwing moths, Pyropteron hispanicum (Kallies, 1999), Pyropteron maroccanum (Kallies, 1999), and Pyropteron meriaeforme (Boisduval, 1840). The main morphological features are described and illustrated with photographs and line drawings. Diagnostic characters of pupae of the studied species and the related species, Pyropteron triannuliforme (Freyer, 1842), are presented.